2010
DOI: 10.1007/s10453-010-9172-0
|View full text |Cite
|
Sign up to set email alerts
|

Airborne fungal spore content in the atmosphere of the city of La Plata, Argentina

Abstract: The aim of this paper is to present the first aeromycological study of the atmosphere of the city of La Plata. Air samples were taken using a Hirst-type volumetric spore trap sampler (Lanzoni, VPPS 2000) for a period of a year (July 2000-June 2001). Seventynine morphological types of spores belonging to the Phyla Myxomycota, Zygomycota, Oomycota, Ascomycota, Basidiomycota, as well as anamorphs of Higher Fungi were identified. A total of 171670.21 spores were recorded, with a daily mean of 540 spores/ m 3 . T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 20 publications
2
21
1
2
Order By: Relevance
“…As for the prevalence of different spore genera, most of the studies agree that Cladosporium make up a very dominant part of the fungal spore air spora, e.g. Sakiyan and Inceoglu (2003); Mallo et al (2010). Other species such as Alternaria, Aspergillus, Ganoderma, Agaricus, Coprinus, Leptosphaeria or smuts and rusts have been considered as important constituents, but usually showed much lower concentrations than Cladosporium (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the prevalence of different spore genera, most of the studies agree that Cladosporium make up a very dominant part of the fungal spore air spora, e.g. Sakiyan and Inceoglu (2003); Mallo et al (2010). Other species such as Alternaria, Aspergillus, Ganoderma, Agaricus, Coprinus, Leptosphaeria or smuts and rusts have been considered as important constituents, but usually showed much lower concentrations than Cladosporium (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Other species such as Alternaria, Aspergillus, Ganoderma, Agaricus, Coprinus, Leptosphaeria or smuts and rusts have been considered as important constituents, but usually showed much lower concentrations than Cladosporium (e.g. Sakiyan and Inceoglu, 2003;Mallo et al, 2010). Based on literature studies, Goncalvez et al (2010) concluded that Asperigllus, Alternaria and Penicillium were predominant in hot climates, whereas Cladosporium spores were found to be most abundant in temperate climatic regimes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spores of Cladosporium are passively launched (i.e, separated from the mycelium via wind currents) and they have mean aerodynamic diameters between roughly 2-4 µm (Fröhlich-Nowoisky et al, 2009;Hameed and Khodr, 2001;Jung et al, 2009b;Reponen et al, 2001). Spores of Cladosporium have been frequently observed as the dominant spore near the ground in sampling studies, where they often comprise at least 35% of the total count as a yearly average (Al-Subai, 2002;Herrero et al, 2006;Li and Kendrick, 1995;Lim et al, 1998;Mallo et al, 2011;Mitakakis and Guest, 2001;Pyrri and KapsanakiGotsi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the southern hemisphere, patterns appear to differ: In La Plata, Cladosporium peaks are recorded in February (Mallo et al, 2011), whilst in Santiago de Chile and also in Australia, peak concentrations are logged in April and May (Rutherford et al, 1997;Ibáñez et al, 2001). At many of the stations in the present study, peak spore concentrations were recorded in summer; similar results have been reported by other authors for Salamanca (Perez-Gorjón et al, 2003).…”
Section: Discussionmentioning
confidence: 99%